Application of BeiDou RNSS timing technology in smart grid lightning locating system - Hao ZHANG; Hongzhen YANG; Weiping SHAO; Jiming YAO (Dianxin kexue)
The smart grid lightning location system is an important power service,and its lightning location accuracy largely depends on the accuracy of time synchronization.Three kinds of BeiDou timing methods were studied and compared,and the RNSS timing method was found to be most suitable for lightning location systems.Furthermore,the principle and characteristics of RNSS timing were studied,and a low-cost user terminal timing hardware and software architecture and algorithm were proposed.The Kalman filter-based BeiDou second pulse signal was used to calibrate the user clock and adjust the voltage through the PID algorithm.The temperature-controlled crystal oscillator made the deviation between the user terminal time and the GNSS time below 100 ns at any time to meet the accuracy requirements of the lightning positioning system.